Security services after the terrorist attacks in the US and Europe. Patriot Act versus the Retention Directive, or the legitimisation of abuses in the sphere of privacy in democratic states: a comparative study (Economic and Political Thought, 2015)
Acceleration of technologisation processes, networking of communication,and in consequences it social interactions, resulted in a shift of social,economic and political paradigm in the civilisation sphere. For the purposeof anticipation of an increasing of more and more sophisticated threats,state law enforcement and intelligence agencies developed and implementednew technologies to allow secret services not only maintain raison d’être butalso to preserve and expand assets. And so the existence of American systemEchelon or the revealed by Edward Snowden PRISM platform openedpublic eyes to the fact that the intelligence agencies (in particular, the USNational Security Agency) are not only able to capture any tele-informationsignal but actually takes advantage of this privilege. Despite these attributes,due to administrative and logistical shortcomings, secret services didnot avoid the embarrassment associated with effectively carried out terroristattacks. Paradoxically, instead of diagnosing the errors within the structures,public sector responded in, previously unknown in democratic countries,increasing the competences of the security forces, de facto legalizing almosttotal surveillance. Symbolic examples are extremely controversial provisionsof the Patriot Act in the US and the EU Retention Directive. As a consequence,the fight against terrorism has become an excuse for blunt violationof standards related to privacy.